Cephalometric evaluation of tongue position and oropharynx space in children treated with Twin-block appliance - Sarvin Sarmadi; Behrad Tanbakuchi; Javad Chalipa; Fahimeh Salimi; Mehrdad Panjnoosh (Tehran University of Medical Sciences, 2018)
Background and Aims: Functional therapy locates the mandible in a more anterior and inferior position. Tongue posture and oropharynx space have a considerable relationship with mandibular posture. The aim of the present study was to determine the changes of tongue posture and oropharynx space following treatment with Twin block appliance in adolescent patients with class II division 1 ma1occlusion. Materials and Methods: Twenty two patients (14 girls mean age:11.5, 8 boys mean age:12.5 years) who were treated with twin-block appliance were enrolled. Cephalograms were used to assess the linear measurements. Graber pattern and McNamara parameter were used to evaluate the tongue posture and oropharynx space, respectively. Data analysis was performed by paired t-test. Results: The findings of the present study showed a significant increase in anterior position of tongue (P=0.06). Oropharynx space was increased significantly (P<0.001). There was a significant correlation between the decrease of ANB and anteroposterior increase of oropharynx space. Conclusion: Twin-block appliance caused considerable forward movement of tongue and significant increase of oropharynx space in the sagittal plan.